Role of Dalbergia sissoo as host species in physiological and molecular adaptation of sandalwood under individual and interactive salinity and water deficit stress - Aarju Sharma; Ashwani Kumar; Sulekha Chahal; Pooja Dhansu; Raj Kumar; Shruti Kaushik; Bindu Battan; Parvender Sheoran; Poonam Choudhary (Plant Stress, 2024)
The aim of present study was to investigate the viability of cultivating white sandalwood (Santalum album L.) in sub-tropical India where farmers are primarily concerned with salinity stress and water deficit as well as different genes that regulate the growth. The present research was undertaken to explore the molecular mechanism of salinity and drought tolerance in sandalwood planted with Dalbergia sissoo (selected based on prior studies) by conducting an RBD experiment under water deficit (50 %), salinity stress (ECiw ∼ 8 ds/m) and combined 50 % water deficit and saline stress (ECiw ∼ 8 ds/m). After two years of imposed treatments, leaves were collected from sandalwood to study the relative gene expression of salinity tolerance (SOS 1, NHX 1 and NHX 2), antioxidant enzymes (SOD, CAT, APX and POX), proline synthesis (P5CS and P5CR) and nitrogen metabolism (NR, NIR, GS and GDH) related genes using real-time PCR (RT-PCR). Different morpho-physiological and biochemical traits showed reduction under individual and interactive stresses except proline and Na+ content as well as anti-oxidative enzyme activities. So far, gene expression studies have not been fully validated in sandalwood under abiotic stresses. The results displayed that SOS 1, NHX 1, NHX 2, APX, POX, CAT, SOD, P5CS and P5CR genes showed maximum expression under combined salinity and water deficit stress. On the other side, genes involved in nitrogen metabolism, i.e., NR, NIR, GS and GDH showed lowest expression under individual as well as interactive water deficit and salinity stress. The current study also highlights the significance of the host D. sissoo which may be good long-term host species in terms of stress tolerance mechanism at molecular level for sandalwood production under changing environmental conditions.